Analysis of GC-FID and GC-MS Microwave-Assisted Hydrodistillation Extraction (MAHD) of Agarwood Chips - Ismail, Nurlaila (International Journal of Integrated Engineering, 2021)
This paper presents an analysis of GC-FID and GC-MS microwave-assisted hydrodistillation extraction (MAHD) of agarwood chips. The work involves of agarwood chips sample preparation starting from drying to soaking process, extraction method using MAHD and compound analysis using GC-FID and GC-MS for compounds identification. During the extraction time, four hours were varied; 2-hours, 3-hours, 4-hours The result showed that the agarwood chips in this study, extracted by MAHD are made up of three major groups; oxygenated sesquiterpenes, monoterpene hydrocarbons, and sesquiterpene hydrocarbons. Not limited to that, the study also adds to the understanding of the variation of the chemical compounds in agarwood especially those contributed to the fragrance of its oil.